Analisis Pengaruh Employee Motivation, Employee Empowerment, Work Life Balance Terhadap Employee Retention Dengan Job Satisfaction Sebagai Variabel Mediasi pada PT XYZ - Orlando Sinaga; Rosdiana Sijabat (JURNAL ADMINISTRASI BISNIS, 2022)
The purpose of this study is to determine the influence of employee motivation, employee empowerment, and work life balance on employee retention which job satisfaction as mediating variables. This research was quantitative study with 178 respondents of permanent employee of PT. XYZ as sample. The questionnaire of this research consisted of 20 items of closed questions using a Likert scale 1-5 and 1 item of open question based on nonprobability sampling with sampling incidental technique. The collected data were then tested for validity and reliability, then analysed using the Structural Equation Modelling (SEM). The results of data analysis on this research shows that employee motivation, employee empowerment, and work life balance has a positive and significant influence on job satisfaction. The positive and significant was also found on the influence of employee motivation, employee empowerment, work life balance, and job satisfaction on employee retention. Job satisfaction significantly and positively mediate the relationship between employee motivation on employee retention. Job satisfaction can mediate between employee empowerment on employee retention and also job satisfaction is proven to mediate the influence of work life balance towards employee retention.